Solving the Travelling Salesman Problem (Tsp) Using Saving Matrix Method (Case Study at Company of Xyz) - Fauzi, Muchammad; Rahmana, Arief; Hartati, Verani (International Journal of Psychosocial Rehabilitation, 2020)
One of the keys to success in implementing supply chain management is to implement a good distribution and transportation network strategy. Transportation and distribution management is designing, organizing, commanding, coordinating, and controlling the process of moving objects or goods from the point of origin to the point of destination to facilitate the delivery of goods and/or services from producers to consumers. The purpose of this study is to show the best routes taken by considering demand and transport capacity. Saving Matrix Methods to obtain the most appropriate and optimal product shipping routes to minimize transportation costs and obtain transportation cost savings. Based on the results of the discussion on the application of the Saving matrix method, the distribution route by considering the demand per week and the transport capacity per one transport is O  B  C  O  D  A  O. Because of the once transport capacity of 105 gallons, after pickup sent to destination B and C, pickups must return to O to load gallons to be distributed to destinations D and A.